2019
DOI: 10.3904/kjim.2018.381
|View full text |Cite
|
Sign up to set email alerts
|

Current status of acute myocardial infarction in Korea

Abstract: Coronary artery disease, especially acute myocardial infarction (AMI), is a leading cause of death in the Asia-Pacific region. The Korea Acute Myocardial Infarction Registry (KAMIR) is the first nationwide, prospective, multicenter registry of Korean patients with AMI. Since the KAMIR first began in November 2005, more than 70,000 patients have been enrolled, and 230 papers have been published (as of October 2018). Moreover, published data from the KAMIR have revealed different characteristics from those of We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 54 publications
5
94
3
3
Order By: Relevance
“…According to a study performed in 2003, the annual incidence of acute pancreatitis in South Korea was 19.4 per 100000 persons[32]. In our patients, the annual incidence of acute pancreatitis was 152.9 (95%CI: 113.4-206.1) per 100000 persons (data not shown).…”
Section: Discussionmentioning
confidence: 47%
“…According to a study performed in 2003, the annual incidence of acute pancreatitis in South Korea was 19.4 per 100000 persons[32]. In our patients, the annual incidence of acute pancreatitis was 152.9 (95%CI: 113.4-206.1) per 100000 persons (data not shown).…”
Section: Discussionmentioning
confidence: 47%
“…However, most of these drugs were administered unless there was a specific contraindication during outpatient clinic term. Fourth, the time from the first symptom onset to hospital or PCI was quite short compared to that of the Korea Acute Myocardial Infarction Registry (KAMIR), which is the nationwide, prospective, multicenter registry of Korean patients with acute MI (symptom onset to balloon time; median 220 min at 2014; 210 min at 2015; 200 min at 2016; and 212 min at 2017) [3]. Differences were found, including short-and longterm MACE, in this registry compared to the KAMIR data.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Acute ST-segment elevation myocardial infarction (STEMI) makes a significant contribution to morbidity and mortality in many parts of the world [1][2][3][4]. It is well known that early diagnosis and proper management, especially delay from the onset of symptoms to revascularization are important for long-term prognosis [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The Gulf Registry of Acute Coronary Events (Gulf RACE) with 6704 ACS patients from six Middle Eastern countries also demonstrated that the absence of typical chest pain was a significant predictor of in-hospital mortality (odds ratio 2.0, 95% CI 1.29-2.75) [16]. Considering the temporal trends of in-hospital mortality that gradually decreased from 4.8% to 3.8% between 2005 and 2018 in KAMIR registry [17], the in-hospital mortality rate (9.2%) in patients with atypical chest pain is still very high, despite patients undergoing treatment with newer drugs and devices than those in the previous decade of NRMI-2 and GRACE study.…”
mentioning
confidence: 99%